Metode Pembelajaran “Bermain Sambil Belajar " - Aulia Putri Rahmawati; Dhita Sukma Anggraeni; Fitriyanti; Rosandra Fidri Silviana; Syalwa Anggun Indiani; Yuwanti (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: Learning is the process of interaction of learners with teachers and learning resources in a learning environment. The learning process needs to be planned, implemented, assessed, and supervised. Good learning will have a good quality of learning. "Play While Learning" is a fun way of singing while playing that helps stimulate the child's brain to more quickly understand the material. Aims :The purpose of this devotion is to know the learning method "Play While Learning" on the Terrace Read Rejosari Grobogan. Method : The method used in this activity by demonstrating how to pronounce alphabet letters well and correctly so as to stimulate children to learn English. The method used in this activity by demonstrating how to pronounce alphabet letters well and correctly so as to stimulate children to learn English. Results: demonstration of the pronunciation of alphabet letters with English can improve children's ability in the participation of learners in following learning by 100%, achieving the target by 75% in the pronunciation of alphabet letters with English. Conclusion: This method of learning is easily accepted and understood so that it can improve the child's ability to understand, read and pronounce alphabet letters in English.